Extracellular secretion of Carocin S1 in Pectobacterium carotovorum subsp. carotovorum occurs via the type III secretion system integral to the bacterial flagellum - Chan, Yung-Chieh; Wu, Huang-Pin; Chuang, Duen-Yau (BMC microbiology, 2009)
Pectobacterium carotovorum subsp. carotovorum is a phytopathogenic enterobacterium responsible for soft rot, a disease characterized by extensive maceration of the affected plant tissue. This species also produces two or more antibacterial substances called bacteriocins, which enhance its competitiveness against related rival species. However, the secretion mechanism for low-molecular-weight bacteriocin is still unknown. A mutant (flhC::Tn5) that did not secrete the low-molecular-weight bacteriocin (LMWB), Carocin S1, was generated by Tn5 insertional mutagenesis. Sequence analysis indicated that this insertion disrupted open reading frame 2 (ORF2) and ORF3 of this strain. Deletion and rescue experiments indicated that ORF2 and ORF3 were both required for extracellular LMWB secretion. The ORF2 and ORF3 sequences showed high homology with the flhD and flhC gene sequences of Pectobacterium carotovorum subsp. atroseptica, Serratia marcescens, Yersinia enterocolitica, and Escherichia coli, indicating that they likely encoded key regulatory components of the type III flagella secretion system. Thus, the extracellular export of Carocin S1 by Pectobacterium carotovorum subsp. carotovorum appears to utilize the type III secretion system integral to bacterial flagella.